Introducing a Novel, Broad Host Range Temperate Phage Family Infecting Rhizobium leguminosarum and Beyond - Ford, Sam; Moeskjær, Sara; Young, Peter; Santamaría, Rosa I.; Harrison, Ellie (Frontiers in Microbiology, 2021)
Temperate phages play important roles in bacterial communities but have been largely overlooked, particularly in non-pathogenic bacteria. In rhizobia the presence of temperate phages has the potential to have significant ecological impacts but few examples have been described. Here we characterise a novel group of 5 Rhizobium leguminosarum prophages, capable of sustaining infections across a broad host range within their host genus. Genome comparisons identified further putative prophages infecting multiple Rhizobium species isolated globally, revealing a wider family of 10 temperate phages including one previously described lytic phage, RHEph01, which appears to have lost the ability to form lysogens. Phylogenetic discordance between prophage and host phylogenies suggests a history of active mobilisation between Rhizobium lineages. Genome comparisons revealed conservation of gene content and order, with the notable exception of an approximately 5kb region of hypervariability, containing almost exclusively hypothetical genes. Additionally, several horizontally acquired genes are present across the group, including a putative antirepressor present only in the RHEph01 genome, which may explain its apparent inability to form lysogens. In summary, both phenotypic and genomic comparisons between members of this group of phages reveals a clade of viruses with a long history of mobilisation within and between Rhizobium species.